Conviction in the absence of proof: Conspiracy mentality mediates religiosity’s relationship with support for COVID-19 conspiracy narratives - Grabow, Hilmar; Rock, Anne (Frontiers in Psychology, 2023)
The belief in conspiracy narratives and the concept of conspiracy mentality have gained increasing attention in psychological science over the last years. A cornerstone is the assumption of secretly acting groups pulling the strings in world affairs. Based on the reasoning that religiosity and conspiracy mentality share a common core – both can be understood as strong convictions without final proof or even in the face of contradictory evidence – we hypothesized that the support of Covid-19 conspiracy narratives would be related to religiosity as well as conspiracy mentality. Given that religious socialization usually starts very early in life we furthermore assumed that religiosity could be an antecedent of conspiracy mentality. Therefore, we tested a mediation model comprising religiosity (predictor), support of conspiracy narratives (criterion), and conspiracy mentality (mediator) among N=616 participants of an online survey. Analyses revealed significant total and indirect effects, supporting our hypothesis.